2022
DOI: 10.1101/2022.08.24.504591
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Site-1 Protease inhibits mitochondrial metabolism by controlling the TGF-β target gene MSS51

Abstract: The mitochondrial response to changes in cellular energy demand is necessary for cellular adaptation and organ function. Many genes are essential in orchestrating this response, including the transforming growth factor (TGFβ) target gene MSS51, which is an inhibitor of skeletal muscle mitochondrial metabolism. Despite the potential importance of MSS51 in the pathophysiology of obesity and musculoskeletal disease, how MSS51 is regulated is not entirely understood. Site-1 Protease (S1P) is a Golgi-resident prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…SREPB1, an important transcription factor regulated by S1P, could induce mitochondrial dysfunction and oxidative stress in ovarian granulosa cells of rats with polycystic ovary syndrome [33]. Furthermore, S1P was also reported as a negative regulator of mitochondrial respiration in skeletal muscle of mice [34]. Above evidence indicated that S1P may be involved in the generation of mtROS.…”
Section: Introductionmentioning
confidence: 99%
“…SREPB1, an important transcription factor regulated by S1P, could induce mitochondrial dysfunction and oxidative stress in ovarian granulosa cells of rats with polycystic ovary syndrome [33]. Furthermore, S1P was also reported as a negative regulator of mitochondrial respiration in skeletal muscle of mice [34]. Above evidence indicated that S1P may be involved in the generation of mtROS.…”
Section: Introductionmentioning
confidence: 99%